Games and insurgencies: towards agonistic participation in the production of space | Jogos e insurgências: por uma participação agonística na produção do espaço - Assis, Ana Paula Silva de (Revista Brasileira de Estudos Urbanos e Regionais, 2015)
By relating games and insurgencies, the intention of this article is to establish a conceptual basis for proposing agonistic participatory tools, with the aim of recovering the emancipatory sense of social participation when producing city space. Through post-political theory and post-democratic criticism we will argue that the institutionalization of participatory processes stands in contradiction to emancipatory ideals, which provide support for social participation as a tool for promoting spatial justice. The concept of open game as formulated by Vilén Flusser will be adopted as a critical, theoretical tool so as to envisage participatory processes that accommodate dissent. Within this context, we will present three game experiences, all of which concern spatial issues. Games, understood as agency, enable insurgent imagery for the city to emerge, facilitate translations and coexistence, and encourage the occupation of public spaces as a possibility for recovering the public sphere.